2023
DOI: 10.1111/bju.15955
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision regret in long‐term survivors after radical prostatectomy: a longitudinal study

Abstract: To investigate prevalence, course, and predictors of longitudinal decision regret in long-term prostate cancer (PCa) survivors treated by radical prostatectomy (RP). Patients and MethodsA total of 1003 PCa survivors from the multicentre German Familial PCa Database completed questionnaires on average 7 years after RP in 2007 and at follow-up 13 years later in 2020. Patients completed standardised patient-reported outcome measures on decision regret, decision-making, health-related quality of life, and psychoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Previous studies have also found that men who had a passive role in treatment decision-making had higher treatment regret than those who assumed an active or collaborative role, and that among those who participated in medical decision-making, 94% did not experience treatment regret [ 54 ]. Our results are in concordance with research that reported an association between treatment decision regret and depression [ 24 , 25 ]. While the evidence for the impact of treatment regret on depression among prostate cancer survivors is evolving, its contribution can be important.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have also found that men who had a passive role in treatment decision-making had higher treatment regret than those who assumed an active or collaborative role, and that among those who participated in medical decision-making, 94% did not experience treatment regret [ 54 ]. Our results are in concordance with research that reported an association between treatment decision regret and depression [ 24 , 25 ]. While the evidence for the impact of treatment regret on depression among prostate cancer survivors is evolving, its contribution can be important.…”
Section: Discussionsupporting
confidence: 93%
“…Research has demonstrated that a large proportion of patients with prostate cancer experience some regret after treatment, and this regret tends to increase over time [ 21 , 22 , 23 , 24 , 51 , 52 ]. Diefenbach and Mohamed (2009) found that prostate cancer survivors who were regretful about their treatment choice(s) had a lower quality of life compared to those who were not regretful [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On multivariable logistic regression, biochemical recurrence, low HRQoL, clinical levels of depression and PSA anxiety (by single item cut-off) were associated with regret. Regarding the in uence of PC-related anxieties (PC/PSA anxiety) on regret, available data are ambiguous: some investigations indicate a clear association between PSA anxiety and regret [4] while others do not [10]. Also, the results typically rely on continuous scaling, rendering the interpretation and comparison of available ndings to the current study and between one another di cult.…”
Section: Discussionmentioning
confidence: 73%
“…Available data suggests that patients may experience decision regret not only during the early postoperative period [2,3,9], but also beyond ve years following primary treatment [4,5]. A recent longitudinal study from our group including 1003 PC survivors showed that decision regret does not naturally resolve, but remains stable or increases slightly even 20 years after RP [10]. Previous studies have shown poor post-treatment oncological and functional outcomes, early health-related quality of life (HRQoL) declines, and PC-related anxiety to be associated with later decision regret [2,3,5,9].…”
Section: Introductionmentioning
confidence: 85%